Pengaruh Kualitas Pelayanan Dan Ketepatan Waktu Jasa Freight Forwarding Terhadap Kepuasan Pelanggan Pada PT Semoga Sukses Logistik - Yogi Priambodo; Resista Vikaliana; I Nyoman Purnaya (Universitas Persada Indonesia YAI, 2022)
This study aims to determine the effect of service quality and timeliness of freight forwardingservices on customer satisfaction. This study involved 30 respondents as research samplesselected based on nonprobability sampling technique, namely saturated sampling. Accordingto Sugiyono, saturated sampling is a sampling technique that is often used when all membersof the population are sampled; the total population is generally relatively small, i.e. less than30 respondents. This study used a correlational quantitative approach. The data analysismethod used included validity test, reliability test, classical assumption test, multiple linearanalysis test, hypothesis test (t-test and f-test), and coefficient of determination test with thehelp of SPSS version 26. The results showed that simultaneously service quality andtimeliness have a significant effect on customer satisfaction with a significance value of 0.36> 0.05 and an Fcount value of 3.781 > Ftable 2.92. Simultaneously price and timeliness alsohave a positive and significant effect on customer satisfaction with a value of 16%; theremaining 84% is influenced by other factors not described in this study. This means that H0is rejected and H3 is accepted